기술표준화, 정부개입, 그리고 공인인증서 - 송영관 (14088, 2015)
Korea witnesses continued debate over the policy that mandates the use of the public authentication certificate (electronic certificate) in electronic financing. The debate mainly centers on the rationale of the government compelling, as a standard, a pub